A digitalization concept for the interaction between users and car-as-a-service - Steinmetz, Charles; Schroeder, Greyce; Rettberg, Achim; Pereira, Carlos Eduardo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais do X Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2020)
Autonomous vehicles are increasingly present in research institutes and industries and this technology may change the way that people use cars and the way that cities are organized. At least a parcel of the future cars will be seen as a service and no longer as a product, so people will use them to go from point A to point B. In this scenario where users can use different cars during the day or the week, according to their needs, there is an integration challenge to offer customized experiences to users regarding their preferences, characteristics, or even to their emotional state. This work proposes a concept of using Digital Twin to have this integration, allowing data related to the vehicle, the user as well as the interaction between them, to be saved during their lifetime. In the end, a case study is presented to illustrate the application of the proposed concept.